ANALISIS PUTUSAN HAKIM PERADILAN PIDANA TERHADAP PENCABUTAN PERKARA DELIK ADUAN ( STUDI PUTUSAN MAHKAMAH AGUNG NO. 1600 K/PID/2009) - Muhammad Yusuf Siregar; Madiasa Ablisar; Mahmud Mulyadi; Utary Maharany Barus (Universitas Sumatera Utara, 2014)
ABSTRACTArrangement complaint about a crime has been arranged expressly in the Book of the Law of Criminal Law Article 72-75 of the Criminal Code. Complaints that have been filed may be withdrawn if still within the grace period of 3 ( three ) months after the complaint is filed ( Article 75 of the Criminal Code). The practice of the law in the Supreme Court decision No. 1600 K/PID/2009. Supreme Court Justice existing legal provisions in the Criminal Code with the advanced legal purpose of restoring the balance that occurs due to a crime and restorative justice teachings that conflict is not simply a crime as a violation of state and public interest but a conflict also represent disrupted and broken relationship between two or more individual in public relations . The panel of judges who handle cases in the decision No.1600 K/PID/2009 has given consideration First Objective of criminal law that is to restore the balance that occurs between the perpetrator and the victim because of the criminal act ; Second : It has been done for peace between the perpetrator and the victim ; Third : To maintain individual relationships within social relationships , especially parties to the conflict are bound family relationship is between the law and the law; Fourth : that the teaching of restorative justice that the judge must be able to facilitate conflict resolution satisfactory to unite the parties to the dispute.